Big in Japan? : Recruitment and training strategies of German companies in Japan - Pilz, Matthias [Verfasser] (My University, 2026)
“The article examines the recruitment and training strategies of German multinational companies in Japan, focusing on the intermediate skill level. It also analyses which factors in the Japanese environment influence these strategies. The EPRG typology and the concept of “institutional logic” serve as the theoretical basis. Twenty-five experts from the field of human resource management (HRM) in ten German companies were surveyed, along with four external experts. The key findings show that German companies in Japan are increasingly hiring older applicants with professional experience. While onboarding is common for all new employees, the dominant form of training for the small number of career entrants is on-the-job training. Moreover, these companies adopt few if any elements of German training modes. These strategies may be understood in terms of institutional logic. The findings are of practical relevance to companies but also offer new insight into theoretical perspectives. The independent strategy pursued by German companies in Japan in the context of recruitment cannot be classified under the EPRG approach: although they do not act like big Japanese companies when recruiting, neither do they implement the strategy of their home country or a global or regional strategy. Their strategy can therefore be termed “independent localisation”, thus expanding the existing EPRG approach.“ (author’s abstract; BIBB-Doku)
Keywords: S 3.2 Unternehmen und Behörden; S 5.3 Personalentwicklung; I 2.3.4 Asien; 370; Unternehmen; Internationales Unternehmen; Personalmanagement; Personalgewinnung; Weiterbildung; Lernen am Arbeitsplatz; Bundesrepublik Deutschland; Japan